Pengaruh Model Pembelajaran Course Review Horay (CRH) terhadap Hasil Belajar Siswa pada Pelajaran IPS di Kelas V di Sanggar Bimbingan Kampung Bharu Malaysia - Khairiyah Nur Hasanah; Indah Pratiwi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The purpose of this study is to examine the role of the Course Review Horay (CRH) learning model in improving student learning outcomes in Social Studies (IPS) for fifth-grade students at the Kampung Bharu Guidance Center in Malaysia. The research design employed is a pretest-posttest for a single group, where students are given a pretest before and a posttest after implementing the CRH model. Data collection was conducted using purposive sampling. This technique is applied when the number of sample members meeting the criteria in the study is 30, with 12 students deemed eligible, thus the entire population is used as the sample. The analysis results indicate a significant improvement between the pretest and posttest scores, suggesting that the CRH model has proven effective in enhancing students' understanding. The interactive learning process encourages mutual support and active participation from students through group discussions and games designed to test their understanding. This study highlights not only the improvement in cognitive learning outcomes but also the development of social skills and students' critical thinking abilities. Therefore, the use of the Course Review Horay (CRH) model is recommended to enhance the quality of learning and students' understanding of education and the learning process as a whole. This study has a significant impact on improving more efficient teaching methods at the elementary education level.